2020
DOI: 10.3390/ma13225077
|View full text |Cite
|
Sign up to set email alerts
|

Selected Physicochemical Properties of Diamond Like Carbon (DLC) Coating on Ti-13Nb-13Zr Alloy Used for Blood Contacting Implants

Abstract: Despite high interest in the issues of hemocompatibility of titanium implants, particularly those made of the Ti-13Nb-13Zr alloy, the applied methods of surface modification still do not always guarantee the physicochemical properties required for their safe operation. The factors that reduce the efficiency of the application of titanium alloys in the treatment of conditions of the cardiovascular system include blood coagulation and fibrous proliferation within the vessel’s internal walls. They result from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Other commonly adopted high-quality coating methods include vacuum deposition and chemical vapor deposition (CVD) [ 45 , 49 , 52 ]. Again, pre-treatments such as plasma etching can still be applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other commonly adopted high-quality coating methods include vacuum deposition and chemical vapor deposition (CVD) [ 45 , 49 , 52 ]. Again, pre-treatments such as plasma etching can still be applied.…”
Section: Methodsmentioning
confidence: 99%
“…Glass is another common substrate used to develop coatings [ 39 , 40 ]. Lightweight metals and alloys with high stability and safety, such as Mg alloys [ 41 , 42 ] and Ti and its alloys [ 43 , 44 , 45 ], are also common substrates. Notably, titanium and titanium alloys are widely applied in biomedical devices, such as cardiovascular stents, lead wires, and artificial blood pumps as a result of their biocompatibility [ 46 ].…”
Section: Materials For Superhydrophobicitymentioning
confidence: 99%
“…Physical methods such as changing the porosity, roughness, and hydrophilicity of internal surface of vascular scaffolds can improve the adhesion of vascular scaffold internal surface and reduce the formation of thrombosis 20,21 . Liu et al 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Physical methods such as changing the porosity, roughness, and hydrophilicity of internal surface of vascular scaffolds can improve the adhesion of vascular scaffold internal surface and reduce the formation of thrombosis. 20,21 Liu et al 22 treated the inner wall of the vascular scaffold by beam interference so that a periodic microstructure was formed on the inner surface of the vascular scaffold. The experimental results showed that the endothelialization process of the treated vascular scaffolds could be completed quickly, the probability of thrombus blockage in vivo was greatly reduced and the long-term patency rate was improved.…”
mentioning
confidence: 99%
“…Previous studies on the deposition characteristics of DLC were mainly carried out on the surface of carbon, silicon and metal materials [11,12,[21][22][23][24][25][26][27]. Due to the different crystal structure of alumina, the surface barrier is different, and the influence law and physical mechanism of ion energy are not clear at present.…”
Section: Introductionmentioning
confidence: 99%